2012
DOI: 10.1080/09585192.2012.676925
|View full text |Cite
|
Sign up to set email alerts
|

Variations in adoption of workplace work–family arrangements in Europe: the influence of welfare-state regime and organizational characteristics

Abstract: Using a unique data set of more than 2800 organizations in 19 countries, this article investigated the variations in adoption of workplace work -family arrangements and whether this variation can be explained either by differences in welfare-state contexts or by organization-related factors. Although the welfare-state context contributed significantly to the explanation of workplace work-family arrangements, the adoption of workplace arrangements was more strongly related to organizational conditions and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 38 publications
7
92
0
1
Order By: Relevance
“…These groups put pressure on organizations to adopt arrangements (normative pressure) beyond the statutory requirements (Oliver, 1991). These argumentations have been used to explaining the observed positive relation between the level of state work-life policies and the provision of work-life arrangements by organizations Den Dulk et al, 2012), and the observed positive relation between the level of national gender equality and the provision of work-life arrangements by organizations (Lyness & Kropf, 2005).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…These groups put pressure on organizations to adopt arrangements (normative pressure) beyond the statutory requirements (Oliver, 1991). These argumentations have been used to explaining the observed positive relation between the level of state work-life policies and the provision of work-life arrangements by organizations Den Dulk et al, 2012), and the observed positive relation between the level of national gender equality and the provision of work-life arrangements by organizations (Lyness & Kropf, 2005).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…With regard to the relationship between state work-life policies (e.g. statutory leave) and organizations' provision of work-life arrangements, some find a positive relationship Den Dulk et al, 2012), while others find a negative relation (Den Dulk, 2001;Ollier-Malaterre, 2009). This leaves the question of how organizations' provision of work-life arrangements is shaped by the national context open for further exploration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations